Where Question, Conditionals and Topics converge - Onea, Edgar (Proceedings of the Amsterdam Colloquium, 2011)
One puzzling fact about German is that what verb-one structures that surface as a yes-no questions can be interpreted as condition als in a topic position. In this paper we provide an analysis for this phenomenon using the basic idea of inquisitive semantics that questions and assertions can be treated on a par as denoting sets of possibilities and some insights about the discourse function of different topic constructions in German. The key assumption is that in topic positions, questions can be interpreted as conditionals if and only if they contain a highlighted alternative possibility. We show that the analysis also correctly predicts the distribution of wh-questions and the distribution of so called irrelevance-conditionals containing auch(‘too’).